Asymmetric biotic interactions and abiotic niche differences revealed by a dynamic joint species distribution model. Issue 5 (2nd April 2018) - Lany, Nina K.; Zarnetske, Phoebe L.; Schliep, Erin M.; Schaeffer, Robert N.; Orians, Colin M.; Orwig, David A.; Preisser, Evan L.
Abstract: A species' distribution and abundance are determined by abiotic conditions and biotic interactions with other species in the community. Most species distribution models correlate the occurrence of a single species with environmental variables only, and leave out biotic interactions. To test the importance of biotic interactions on occurrence and abundance, we compared a multivariate spatiotemporal model of the joint abundance of two invasive insects that share a host plant, hemlock woolly adelgid (HWA; Adelges tsugae ) and elongate hemlock scale (EHS; Fiorina externa ), to independent models that do not account for dependence among co‐occurring species. The joint model revealed that HWA responded more strongly to abiotic conditions than EHS. Additionally, HWA appeared to predispose stands to subsequent increase of EHS, but HWA abundance was not strongly dependent on EHS abundance. This study demonstrates how incorporating spatial and temporal dependence into a species distribution model can reveal the dependence of a species' abundance on other species in the community. Accounting for dependence among co‐occurring species with a joint distribution model can also improve estimation of the abiotic niche for species affected by interspecific interactions.